2022
DOI: 10.1039/d2fo00888b
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopreventive properties of hydroxytyrosol and mannitol-rich extracts obtained from exhausted olive pomace using green extraction methods

Abstract: Exhausted olive pomace (EOP) is produced in the olive-pomace oil extractors as by-product. However, the obtention of bioactive compounds from EOP can reinsert it into the economy as a new...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Besides the antioxidant capacity of olive phenolic compounds in biological and food systems [84,85], olive phenolic compounds present a wide range of pharmacological properties, as reviewed in [12,86]. As an example, Tab.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the antioxidant capacity of olive phenolic compounds in biological and food systems [84,85], olive phenolic compounds present a wide range of pharmacological properties, as reviewed in [12,86]. As an example, Tab.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The extraction will reduce the complexity of the original biomass, concentrating the compounds of interest. At the same time, the solid fraction will be enriched in non-nutritive components such as lignin, cellulose, and hemicellulose [85]. Tab.…”
Section: Examples Of Industrial Applications Of Olive Bioactive Compo...mentioning
confidence: 99%
“…The phenolic profiles were acquired using two methodologies, one using high-performance liquid chromatography (HPLC) and UV detection and the other based on HPLC-quadrupole time-of-flight (QTOF)-mass spectrometry (MS), according to a previous study [15]. The former analysis was performed in a Prominence UFLC chromatograph (Shimadzu Corporation, Kyoto, Japan) using a BDS HYPERSIL column (C18 with 5 µm particle size; dimensions, 4.6 mm × 250 mm) (Thermo Fisher Scientific Inc., Waltham, MA, USA).…”
Section: Phenolic Content Composition and Antioxidant Assaysmentioning
confidence: 99%
“…The former analysis was performed in a Prominence UFLC chromatograph (Shimadzu Corporation, Kyoto, Japan) using a BDS HYPERSIL column (C18 with 5 µm particle size; dimensions, 4.6 mm × 250 mm) (Thermo Fisher Scientific Inc., Waltham, MA, USA). The gradient conditions and mobile phases were in accordance with previous studies [14,15]. The commercial standards of trans-resveratrol and trans-ε-viniferin were obtained from Extrasynthese (Genay, France) and used for quantification in the aforementioned chromatographic conditions at 280 nm.…”
Section: Phenolic Content Composition and Antioxidant Assaysmentioning
confidence: 99%
“…HT shows anti-fibrotic and anti-inflammatory effects by regulating oxidative stress in the liver (24). HT has also been shown to have a protective effect against liver damage (25). Another study has shown a combined HT and Vitamin E application to reduce fibrosis associated with non-alcoholic fatty liver disease (26).…”
Section: Introductionmentioning
confidence: 99%